Investigation of a tunable and switchable multi-wavelength bidirectional Brillouin-erbium fiber ring laser - Wang, F.; Yuan, R. Y. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
A multi-wavelength bidirectional Brillouin-erbium fiber ring laser with switchable Brillouin frequency spacing (BFS) is proposed and experimentally demonstrated. In the presented Brillouin-erbium ring laser, including an optical amplifier and a highly nonlinear fiber, and without any optical isolator, due to Rayleigh scattering, stimulated Brillouin scattering, and cascaded four-wave mixing initiated successively by the Brillouin pump (BP) light, the odd- and even-order Stokes lines are generated and circulate in the opposite direction in the ring cavity. The BP light and Stokes-induced Rayleigh backscattering light also simultaneously circulate in the ring cavity. Only by adjusting BP power, the gain competition between Brillouin based Stokes and cavity modes’ oscillation can be controlled, the laser output can be conveniently switched between single BFS and odd- or even-order double BFS. In addition, under the certain BP power conditions, the proposed multi-wavelength Brillouin-erbium fiber laser also can realize switchable odd- or even-order Stokes generation and Stokes generation with single BFS, with an increasing wavelength number in turn, only by simply adjusting pump power of the erbium-doped fiber amplifier. Stability and wavelength tunability of the proposed multi-wavelength bidirectional Brillouin-erbium fiber ring laser are also investigated, respectively.
Optica Applicata, Vol. 51, 2021, nr 3, s. 375-390
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Rayleigh scattering; stimulated Brillouin scattering (SBS); four-wave mixing (FWM); lasers and laser optics